The Influence of the 6-month Course of Nordic Walking on Patient with Parkinson's Disease - a Case Report - Paula Musiał; Monika Michalik; Ewelina Nowak; Justyna Szefler-Derela (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2017)
A person with Parkinson's disease has bigger problems with maintaining the stability than the healthy person. Nordic Walking is a safe kind of physical activity for elderly people. The aim of this study is to present the influence of a 6-month therapy of the Nordic Walking on the imbalance and the risk of falls for 66-years-old patient with Parkinson's disease. On the basis of results of 4 tests, performed both at the beginning and at the end of the Nordic Walking therapy, we have made a comparison of patient's changes before and after 6 months of rehabilitation. the DGI test, the PD patient received 18 points. After he got 22 points. In the Functional Reach Test ( FR), while attempting to reach forward, reached out for 23 cm before the therapy, and 31 cm after the therapy. In the test and go up the patient got a time of 63 seconds, after therapy the time was reduced to 45 s. Nordic Walking is a safe kind of physical activity for people with Parkinson's disease. It reduces muscle tension, and improves joint function.